Bioconsolidation of soil microflora and subsequent increase in the efficiency of humification of cereals plant residues - Zhemyakin S.V.; Vorobyov N.I.; Popov A.A.; Orlova O.V.; Rusakova I.V. (BIO Web of Conferences)
An experimental and theoretical study of the technology of using the micromycete-bacterial biopreparation Mycobact (St. Petersburg Biotechnologies LLC), designed to intensify the processes of humification of straw and stubble of grain crops in natural field conditions, as well as to reduce the level of concomitant release of greenhouse gas CO2 from the soil, As a result of the study, it was found that the configuration biosystem image of the biopreparation Mycobact can persist in it for a long time, and when inoculated with a biopreparation of grain straw, it can provoke the unification of native soil microflora into effective biosystems that control humification processes with a low level of release of greenhouse gas CO2 from the soil. Neural network computing tools have succeeded in converting fractal profiles of soil microorganisms by converting fractal profiles of microorganisms into CSIcon, CSIgum, CSIco2 indices, which provide an opportunity for quantitative comparison of experiment options and selection of agricultural practices that meet increased requirements for the intensity of humification processes in the soil and the level of CO2 release into the atmosphere. According to the results of the study, it can be argued that the use of the microbiological preparation Mycobact accelerates the processes of humification of straw and stubble of grain crops in natural field conditions and helps to reduce the release of greenhouse gas CO2 from the soil into the atmosphere.